Optimal control problem for systems governed by nonlinear parabolic equations without initial conditions - Bokalo, M.M.; Tsebenko, A.M. (Carpathian Mathematical Publications, 2016)
An optimal control problem for systems described by Fourier problem for nonlinear parabolic equations is studied. Control functions occur in the coefficients of the state equations. The existence of the optimal control in the case of final observation is proved.